A study of assessor training strategies and its effect on accuracy, discriminant validity and interrater reliability in UMP - Nur Ashida Ayu, Abdul Rani (2015)
The purpose of this study was to explore whether the implementation assessor training is suitable to be conducted in University Malaysia Pahang (UMP). Specifically, this study examines the utility of two assessor training strategies; frame of reference training (FOR) and rater error training (RET) in staff selection process. Results are obtained by opinion from 84 assessors in each department in UMP. The two approaches are compared each other and analyzed based on 3 dependent variables. A general framework is presented in term of two training strategies in the effects of accuracy, discriminant validity, and interrater reliability. Several hypothesis was performed and proved that both training are accepted by the assessors in UMP and the accuracy, discriminant validity, and interrater reliability had influenced both training. However, those assessors feels that they prefer to have FOR Training in the future as it is seen as a structured and coordinated training compared to RET.